Bonding Reactions of Dental Self-Adhesive Cements with Synthetic Hydroxyapatite as a Function of the Polymerization Protocol. (10th November 2021) - Borges, Roger; Graeff, Carlos Frederico de Oliveira; Marchi, Juliana; D'Alpino, Paulo Henrique Perlatti
Abstract : Objectives . This study evaluated the influence of the cement composition and different polymerization protocols on the bonding chemical interaction of self-adhesive cements with synthetic hydroxyapatite. Materials and Methods . Two commercial self-adhesive resin cements (RelyX U200 and Maxcem Elite) were selected, manipulated, mixed with hydroxyapatite dry powder (HAp), dispensed into molds, and distributed into three groups according to polymerization protocols: immediate photoactivation (IP); delayed photoactivation, 10 min self-curing and light-curing (DP); and chemical activation (CA, no light exposure). The detailed chemical information, at atomic scale, on the surface and deeper into the bulk of self-adhesive cement/hydroxyapatite mixtures was evaluated with X-ray photoelectron spectroscopy (XPS). Results . Chemical elements were detected in both cements, such as Na, O, Ca, C, P, and Si. Other elements were detected in minor concentrations. RelyX U200 exhibited the most intense formation of calcium salts products when the cement/HAp mixtures were photoactivated (immediate or delayed). RelyX U200/HAp mixture under delayed photoactivation (DP) also exhibited higher binding energy between calcium moieties of the HAp and methacrylates in the cement. A higher energy difference in the interaction of HAp with the cement comparing the bulk and surface areas was observed when RelyX U200 underwent the delayed photoactivation protocol. Maxcem Elite exhibited an increased chemical reactivity when either chemically activated or immediately photoactivated and a higher binding energy of the carboxyl groups bonded to the calcium of HAp when chemically activated. Conclusions . The interaction of cements with hydroxyapatite is chemical in nature and leads to the formation of calcium salts, which may favor better integrity and longevity of adhesive restorations. The polymerization protocol affects the chemical interaction in mixtures of self-adhesive cements and hydroxyapatite, influencing the formation of these salts and the establishment of intermolecular interactions between the HAp and the cements.